Pengaruh Pengendalian Internal, Moralitas Individu Dan Personal Culture Terhadap Kecenderungan Kecurangan LPD - Ni Putu Widyarini; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2023)
Research purpose is to confirming effect of internal controls, individual morality also personal culture on the tendencies of frauds in LPD at Banjarangkan Regency. This research was conducted at LPD in Banjarangkan Regency. The method used is a quantitative method. The data used is primary data using a questionnaire as a data collection method. The population in this study were all employees at LPD Banjarangkan Regency as many as 115 employees. The sampling technique used is random sampling with the slovin formula so that the number of samples is 53 respondents. The analysis technique used is Multiple Linear Regression. Result confirm influence of internal control, individual morality and personal culture had a positive and significant effect on the tendency of fraud.